Hepatitis B Virus Reactivation in Cancer Patients Treated With Immune Checkpoint Inhibitors. Issue 3 (April 2021) - Burns, Ethan A.; Muhsen, Ibrahim N.; Anand, Kartik; Xu, Jiaqiong; Umoru, Godsfavour; Arain, Abeer N.; Abdelrahim, Maen
Abstract : There have been unique adverse events reported with targeted blockade of programmed death-1 (PD-1), programmed death-ligand-1 (PD-L1), and cytotoxic T-lymphocyte-associated protein-4 (CTLA4), including immune mediated toxicities. Recently, there have been reports of hepatitis B reactivation (HBVr) occurring with PD-1/PD-L1 inhibitors, which may result in treatment delays, interruptions, or discontinuation. This retrospective literature review and analysis of the Food and Drug Administration's (FDA) Adverse Events Reporting System (FAERS) queried reported cases of "Hepatitis B reactivation" reported with the PD-1/PD-L1 inhibitors "Pembrolizumab, " "Atezolizumab, " "Nivolumab, " "Durvalumab, " "Avelumab, " and "Ipilimumab" from initial FDA approval to June 30, 2020. Disproportionality signal analysis was determined by calculating a reporting odds ratio (ROR) and 95% confidence intervals (CI). The ROR was considered significant when the lower and upper limits of the 95% CI were >1 and confirmed by the Fisher exact test ( P <0.05). Pembrolizumab had a strong signal associated with HBVr, with a ROR of 2.32 (95% CI: 1.11–4.28) ( P =0.013) and was the only statistically significant finding. There were no reports of HBVr with Ipilimumab or Avelumab. Additional prospective studies should be conducted to validate the findings of this retrospective pharmacovigilance analysis to determine the risk of HBVr in patients receiving immune checkpoint inhibitors. Abstract : Supplemental Digital Content is available in the text.